Development of waste brine to energy system with Concentric Cylindrical Thermoelectric Generator (CCTEG) at Ulubelu Geothermal Power Plant - Resha, Mochammad; Soelaiman, Tubagus Ahmad Fauzi; Riyanto, Hendi; Parman, Parman (ARKA INSTITUTE, 2025)
The Ulubelu geothermal field plan to utilize geothermal energy through the direct use energy of brine. Develop waste to energy a Thermoelectric Generator (TEG) into the system represents an innovative approach to harness additional energy from the high-temperature brine before it is reinjected into the well. The Circular Construction Thermoelectric Generator (CCTEG) is designed using a double-pipe heat exchanger, with diameters of 1.02 m for the brine and 0.91 m for the cold water. The brine enters at 174°C with a mass flow rate of 763 kg/s, while the condensate water from the cooling tower is at 28°C. Simulation results show that the CCTEG requires 2309370 TEG semiconductors along a 32-meter length, achieving a power output of 538.25 kW with a total voltage of 51.2 kV and a current of 10.5 A. The system experiences pressure drops of 189 kPa on the hot side and 1,869 kPa on the cold side, utilizing 0.6% of the total brine energy potential of 79760 kW. This design demonstrates an efficient method to optimize energy extraction from geothermal resources.